PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INGGRIS BERWAWASAN EKOWISATA DAN KEARIFAN LOKAL PADA KOMUNITAS RUMAH BAMBU DESA TANAH RATA MALUKU TENGAH - Nurlaila Tuanany (IAKN Ambon, 2022)
This study aims to develop an English language learning module with ecotourism and local wisdom insights in the Bamboo House Community of Tanah Rata Village, Pulau Banda District, Central Maluku Regency. The development research carried out was intended to find out the needs of students for learning modules that have an ecotourism and local wisdom perspective, obtain data and conclusions about the modules that have been used, compile and develop modules that emphasize the concept of ecotourism and local wisdom in accordance with the characteristics of Banda Island as well as one of the tourism icon in Maluku province, get the validity of the test results from media and material experts, get the results of field tests on the modules that have been developed, and get the feasibility results of the modules. The method used in this research is Research and Development (R&D). The development procedure used is the ADDIE development model, namely analysis (needs analysis), design (designing learning modules), development (developing learning modules), implementation (implementing learning modules in small groups and large groups), and evaluation (evaluating the use of existing modules). developed). The modules that have been developed include ecotourism-oriented English materials and local wisdom that support the Banda Island tourism sector. Topics raised included Ecotourism and Local Wisdom, Beach Watersport, Enjoy Your Stay, Marine Tourism, Water Transportation, Lawataka Festival, Historical Tourism, Natural Resources. The results of the validation carried out by media experts and material experts fall into the